2016
DOI: 10.5539/jel.v6n2p53
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Education Curricula: Human Rights and Citizenship in Early Childhood Education

Abstract: This study examines the human rights and the notion of citizenship under the prism of pedagogical science. The methodology that was followed was the experimental method. In a sample of 100 children-experimental group and control group held an intervention program with deepening axes of human rights and the concept of citizenship. The analysis of the findings presented in four axes. The first relates to the analysis of the responses of the two groups using quantitative data. The second axis concerns the discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…The results of this research are similar to the findings of Sounoglou and Michalopoulou (2016) who investigated about human rights and the notion of citizenship under the prism of pedagogical science in Greece and concluded that children seem to understand in a pedagogical context the concept of human rights and the concept of citizenship in its capacity to influence school and not only in everyday life, respect the wishes of others, understand the limits and restrictions in the school and the local community; participation as a social obligation, but also a right, to the understanding of human rights and the rights of the child as a premise for the quality of their lives and the improvement of the knowledge and skills of teachers to teach civic education is still a challenge.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this research are similar to the findings of Sounoglou and Michalopoulou (2016) who investigated about human rights and the notion of citizenship under the prism of pedagogical science in Greece and concluded that children seem to understand in a pedagogical context the concept of human rights and the concept of citizenship in its capacity to influence school and not only in everyday life, respect the wishes of others, understand the limits and restrictions in the school and the local community; participation as a social obligation, but also a right, to the understanding of human rights and the rights of the child as a premise for the quality of their lives and the improvement of the knowledge and skills of teachers to teach civic education is still a challenge.…”
Section: Discussionsupporting
confidence: 90%
“…Rodríguez (2014) raised the understanding of the conception that citizens have of a group of community mothers of the Technical Program in Comprehensive Early Childhood Care and found that the identification of the activities they developed for citizenship training was based on of participation, autonomy and thinking care, concluded that women guide this learning towards the duty of the citizen, towards the construction of normative thinking that tells you how to act and what not to do, what values to have and what qualities to build. Sounoglou and Michalopoulou (2016) examined human rights and the notion of citizenship under the prism of pedagogical science, concluded that children are affected in their participation by the micro-level curriculum which affects their behavior at the macro level, children seem to understand in the pedagogical context the concept of human rights and the concept of citizenship related to their ability to influence the school and not only in everyday life, respect the wishes of others, understand the limits and restrictions in the school and the local community; participation as a social obligation and as a right, the understanding of human rights and the rights of the child as a premise for the quality of their lives and the improvement of knowledge. Lay (2015) sought to know the social representations and discursive positions that childhood builds from participation, as the main finding found that the different discursive positions that account for childhood participation are grouped in two, one centered and adult type another dissident type.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it invites a fluid view (Duckles et al, 2019) of learning environments and teachers' improvisatory practices (MacRae et al, 2018), valuing children's unexpected place negotiations that unfold new alternative spatialities. Acknowledging that children live citizenship as heterotopians in their learning environments, and therefore are already-citizens empowered with democratic values (Sounoglou & Michalopoulou, 2016), inevitably calls for pedagogies to entangle less as consumers of given learning environments and more as heterotopic place-makers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Reggio Emilia pedagogical philosophy, which internationally expanded children's engagement in co-creating the third teacher, also unfolds creative citizenship. We argue that its understanding bases on a human-rights notion of citizenship (Sounoglou & Michalopoulou, 2016) that approaches space and place politics of children acknowledging kindergarten's right to designing its own environment (Hoyuelos, 2005) and children's right to grow, learn and inhabit aesthetically beautiful and provoking spaces. Though Reggio Emilia aims for deep responsiveness to children's multimodal expressiveness -the 100 languages of children- (Wood et al, 2015), it presumes human-centered environments where children flow and dwell thought-provoking designed spaces and relational pedagogies (Edwards et al, 1998;Gandini, 2011).…”
Section: Larkins' Inspiring Work On Citizenship Draws On Critical Realist Theorymentioning
confidence: 99%
“…En este sentido, la subordinación de políticas de educación a las necesidades del mercado y la falta de voluntad política por parte de los gobiernos, ha conducido a que la perspectiva de la educación de la primera infancia como derecho humano, haya sido suplantada en gran medida por una visión economicista y utilitaria de la educación, basado en la idea de crear capital humano. Sin embargo, el concepto de educación y cuidado de la primera infancia, cuando se basa en la perspectiva de derechos humanos, no sólo tiene la posibilidad de preparar a las personas para sus vidas futuras y para construir mejores condiciones económicas, sino que considera la promoción de la igualdad, la superación de la pobreza y la equidad social (Bakken et al, 2017;Sounoglou & Michalopoulou, 2017). Una visión reductora de la educación en la primera infancia, minimiza el papel de los actores principales -los niños y las niñas -y les impide ejercer una participación activa, valorando su futuro y no su presente, alimentando así grandes asimetrías estructurales, que generalmente están en la raíz de la exclusión y discriminación.…”
Section: Políticas Neoliberales Y Primera Infancia Ensaiounclassified